Effect of Integrated Nutrient Management on Growth, Yield Attributes, Yield and Economics of Off-season Cauliflower (Brassica oleracea var. Botrytis L.) Grown under North Eastern Ghat Zone of Odisha - Mukhi, S. K.; Sardar, S. S.; Mishra, P. J.; Bar, N; Mishra, D. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during 2019 (July–October) at farmer’s field in Kandhamal district of Odisha under Krishi Vigyan Kendra, Kandhamal, Zone-V, Kolkata, OUAT, Bhubaneswar, Odisha, India to study the effect of integrated nutrient management on growth, yield attributes, yield and economics of off-season cauliflower (Brassica oleracea var. Botrytis L.). The experiment was laid out in Randomized Block Design (RBD) consisted of four treatments with seven replications. The treatments comprised of T1: Farmer’s practice (FYM @ 1 t ha-1 and fertilizer @ 60-40-30 kg N-P2O5K2O ha-1), T2: 100% RDF @120:60:60 kg N-P2O5-K2O ha-1, T3: Soil test based NPK+FYM @5 t ha-1 and T4: Soil test based NPK+FYM @5 t ha-1+Boron. From the experiment it was found that integrated application of chemical fertilizers as per soil test results, organic manures (FYM @ 5 t ha-1) and micronutrient (boron) was the best option for achieving better yield. The highest plant height (57.3 cm), number of leaves plant-1 (22.7), leaf length (35.6 cm), curd yield (188.4 q ha-1), marketable curd weight (635.4 g), net return (` 1,48,260 ha-1) and B C ratio (1:3.2) were recorded with the treatment T4 followed by and T2. Whereas, the lowest values of growth parameters like plant height (40.7 cm), number of leaves plant-1 (16.2), leaf length (26.1 cm), curd yield (140.2 q ha-1), marketable curd weight (466.8 g), net return (` 1,01,130 ha-1) and B C ratio (1:2.7) were recorded with the treatment T1.